Pengaruh Konflik Peran Ganda Terhadap Kinerja Wanita Berperan Ganda Yang Dimediasi Oleh Variabel Stres Kerja - Pusponegoro, Martanti; , Rini Kuswati, S.E., M.Si (2015)
Goals to be achieved in the implementation of this research are: (1) To analyze the effect of the conflict on the performance of the dual role women play doubles. (2) To analyze the effect of the conflict on the dual role of occupational stress. (3) To analyze the effect of work stress on the performance of the double role of women. (4) To analyze the stress of work to mediate the conflict peengaruh dual role on the performance of the double role of women. This study uses survey approach. The population in this study were women who work and have a family at PT Sari Warna Asli Boyolali. Samples were taken of 100 people, with a purposive sampling method, sampling is limited to specific types of informants who fit the study criteria and convenience sampling, which took the respondents in the sample by coincidence. Data analysis techniques used in this study: (1) Test the quality of the data used to test the validity of the instrument with corrected item total correlation, Cronbach alpha reliability test and the Kolmogorov Smirnov normality test, (2) hierarchical regression test (Hierarchical Regression), (3) Test Mediation, (4) Test the hypothesis, using the t test, F test, and test the coefficient of determination (R2). The results showed that: (1) a dual role conflict significantly affect the performance of the double role of women. (2) the dual role conflict significantly influence job stress. (3) Work stress significantly affect the performance of the double role of women. (4) Work stress mediates the influence of dual role conflict partially on the performance of the double role of women, as well as evidenced by the F test that dual role conflict and job stress simultaneous effect on the performance of the double role of women.